THU0652-HPR ONLINE EDUCATION YIELDS SIGNIFICANT GAINS IN RHEUMATOLOGISTS' KNOWLEDGE OF BIOLOGICS AND BIOSIMILARS BUT A SUBSTANTIAL GAP REMAINS. (2nd June 2020) - Stan, A.; Bell, E.; Schoonheim, P.; Mysler, E.
Abstract : Background: Biologics are complex proteins which have revolutionized the treatment of many serious diseases. Due to their complexity and manufacturing which involves living organisms, it is not possible to create identical versions of reference biologics, but it is possible to create biosimilar drugs. Biosimilars have the potential to yield high cost savings and expand treatment options to meet the growing demand for biological therapies. Objectives: This study assessed whether the online CME-accredited round-table-discussion titled "Understanding Biologics: from protein to clinical practice" improved physicians' understanding of the inherent variability of biologics and what similarity means in the context of biologics as well as the analytical assessment of quality that applies to both biologics and biosimilars. Methods: Rheumatologists participated in an online CME activity (www.medscape.org/viewarticle/900121 ) consisting of a 30-minute video discussion between 4 experts with accompanying slides. Educational effect was assessed using a 4-question repeated pairs, pre-/post-assessment. A chi-square test was used to determine if a statistically significant improvement ( P <.05 significance level) existed in the number of pre-/post-test correct responses. Cramer's V was used to estimate the level of impact of the education. The CME activity launched on 22 Aug 2018, and the data were collected through 9 Oct 2018. Results: A total of 622 rheumatologists participated in the educational activity, and 87 completed the pre- and postassessment. Overall the activity had a signficiant impact ( P <.001) on rheumatologists' understanding of the inherent variability of biologics and the regulatory requirements for approval of a biosimilar. The Cramer's V value of 0.186 indicates a considerable effect of the education. The average perecentage of correct responses rose from 33% pre-activity to 51% post-activity. A linked learning assessment (individual responses matched pre- and post-education) showed that 25% of learners improved their knowledge and 26% reinforced their knowledge. The change in percentage of correct responses from pre- to post-assessment achieved statistical significance ( P <.05) in 2 of the 3 questions presented: (i) understanding the type of studies needed to demonstrate comparability of a biosimilar to an originator (11% at baseline; 45% post activity), (ii) understanding the type of variability considered acceptable for a biologic (46% at baseline; 63% post activity). However, no knowledge gain was observed regarding basic analytic attributes evaluated to ensure batch to batch consistency (37% at baseline; 38% post activity). Almost 45% of rheumatologists gained confidence in their ability to describe the regulatory requirements for approval of a biosimilar. Conclusion: This online CME activity significantly improved rheumatologists' understanding of the inherent variability of complex biologic medicines and the role of analytical studies in the regulatory approval of biosimilars. However, there is room for further improving physicians' knowledge, especially of basic analytics of biologics and biosimilars. Acknowledgments: This CME-certified activity was supported by independent funding from Sandoz. Disclosure of Interests: Adriana Stan Grant/research support from: The CME-certified activity was supported by an independent educational grant from Sandoz., Elaine Bell: None declared, Peter Schoonheim Grant/research support from: This CME-certified activity was supported by independent funding from Sandoz., Eduardo Mysler Grant/research support from: AbbVie, Lilly, Pfizer, Roche, BMS, Sandoz, Amgen, and Janssen., Consultant of: AbbVie, Lilly, Pfizer, Roche, BMS, Sandoz, Amgen, and Janssen.